2019
DOI: 10.1002/lipd.12138
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Dietary Fish Oil with Vegetable Oil Blends in Female Rainbow Trout Brood Stock Does Not Affect Breeding Quality

Abstract: To determine the effects of replacing fish oil (FO) with a mixture of vegetable oils (VO) in plant protein‐rich diets on reproductive performance, the fatty acid profile of embryos as well as health indices of female rainbow trout (Oncorhynchus mykiss) brooders (initial mean body weight, 1.8 ± 0.1 kg), a 3‐month feeding trial was conducted. Four isoproteic (ca. 42%) and isoenergetic (ca. 20 MJ/kg) diets were formulated in which 50% (FO50/VO50), 75% (FO25/VO75), and 100% (VO100) of FO were replaced by a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
5
11
0
Order By: Relevance
“…The proportions of SFA increased in embryos during the day 20 and the hatching day (day 35; Table ). In agreement with our results, several studies in other cold water fish species such as Clupea harengus (Tocher, ), Salmo salar (Murzina et al, ) and O. mykiss (Agh et al, ; Noori et al, ) documented a proportional increase in SFA during embryogenesis. The augmentation of the SFA biosynthesis in de novo pathway may result in an increase in the SFA concentrations in embryos, which could provide their energy requirement for hatching (Cejas et al, ; Murzina et al, ; Sargent, Tocher, & Bell, ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The proportions of SFA increased in embryos during the day 20 and the hatching day (day 35; Table ). In agreement with our results, several studies in other cold water fish species such as Clupea harengus (Tocher, ), Salmo salar (Murzina et al, ) and O. mykiss (Agh et al, ; Noori et al, ) documented a proportional increase in SFA during embryogenesis. The augmentation of the SFA biosynthesis in de novo pathway may result in an increase in the SFA concentrations in embryos, which could provide their energy requirement for hatching (Cejas et al, ; Murzina et al, ; Sargent, Tocher, & Bell, ).…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, Lazzarotto et al () reported female brooders of O. mykiss fed only vegetal‐based feeds containing blends of VO over a 3‐year reproduction period had successful larvae production by biosynthesizing LC‐PUFA from their precursors in the feed and incorporating them into the ova. Furthermore, previous studies in our laboratory also demonstrated substitution of dietary FO up to 75% with different mixture of VO in PP‐rich diets supported successful reproduction performance in O. mykiss females (Agh, Jafari, Jalili, Noori, & Mozanzadeh, ; Noori et al, ). In contrast to our previous research, in this study we increased the proportions of linseed and sunflower oils as good sources of α‐linolenic (ALA) and linoleic (LNA) acids in the mixture of VO for increasing the content of PUFA in the experimental diets.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations